Néotène, Hybrides et Chimères - Marika Moisseeff (Ateliers d'Anthropologie)
In the West, the idea of man as a creature made by God in His own image has progressively given way to a biological conception that locates humanity’s specific place and ontology between those pertaining to two distinct species: the primates that preceded humans in the course of phylogenesis, and the species that will descend from them, such as the transgenic or chimerical entities that biotechnology should allow them to create. Like other myths in other times and places, works of science fiction portray hybrid beings that, in this case, reveal contemporary Western understandings of human nature. It is from this perspective that the author explores one such account, Les fables de l’Humpur, which chronicles the end of humanity following a rebellion of the chimeras produced to relieve “true” or “pure” humans from thankless drudgery.